Foreign Counterfeiting of Status Goods - Grossman, Gene M.; Shapiro, Carl (Quarterly Journal of Economics, 1988)
We study the positive and normative effects of counterfeiting, i.e., trademark infringement, in markets where consumers are not deceived by forgeries. Consumers are willing to pay more for counterfeits than for generic merchandise of similar quality because they value the prestige associated with brand-name trademarks. Counterfeiters of status goods impose a negative externality on consumers of genuine items, as fakes degrade the status associated with a given label. But counterfeits allow consumers to unbundle the status and quality attributes of the brand-name products, and alter the competition among oligopolistic trademark owners. We analyze two policies designed to combat counterfeiting: enforcement policy which increases the likelihood of confiscation of illegal items, and the imposition of a tariff on low-quality imports.